The gut of C. elegans as a potential refuge for antibiotic-resistant bacteria - Korpinen, Tuuli (My University, 2026)
The rapid spread of antibiotic resistance in both environmental and clinical settings represents one of the most pressing challenges of the century. Antibiotic resistance is often associated with a fitness cost in bacteria, suggesting that sensitive bacteria should exclude resistant bacteria in the absence of antibiotics. However, numerous studies have shown that resistant bacteria can persist in the environment even in the absence of antibiotics, challenging the idea that controlling antibiotic overuse would solve the current health crisis. There is a pressing need to understand the various mechanisms that contribute to maintaining antibiotic resistance in the environment to manage its further spread. Bacterial predators are important regulators of microbial communities, yet their contribution to maintaining antibiotic resistance remains poorly understood. Studying the role of bacterial predators provides insights into how antibiotic resistance persists in the environment. This thesis aimed to investigate how a bacterial predator, Caenorhabditis elegans, influences the distribution of antibiotic resistance traits within bacterial communities. By studying three bacterial species with a spectrum of fitness costs, I aimed to assess the competitive dynamics between species inside and outside the gut of C. elegans and determine whether the gut provides a refuge for antibiotic-resistant bacteria through altered bacterial competition. I performed pairwise competition experiments in the presence of the predator, of which I quantified the relative abundances of each species to assess shifts in competitive dynamics inside and outside the gut. Overall, these results suggest that C. elegans predation alters pairwise interspecies interactions, promoting species diversity and persistence of antibiotic-resistant bacteria. This thesis provides a plausible mechanism explaining how altered bacterial competition contributes to maintaining antibiotic resistance.
Keywords: Bacterial competition; bacterial predation; antibiotic resistance; cost of resistance